Deradicalization: not soft, but strategic - Dechesne, Mark (Crime, law and social change, 2011)
The present article considers deradicalization programs. It is observed that deradicalization is primarily a strategic tool, that it was already used in the 1970s, that it can occur spontaneously, and that is should be differentiated from physical disengagement. An evaluation of existing deradicalization programs lead to the propositions that 1) deradicalization programs in the area of right-wing extremism primarily focus on changing behavior not thoughts, that 2) currently there is insufficient insight in what motives people to deradicalize, and 3) that insights from psychology are still insufficiently used to increase effectiveness of deradicalization. Research can make an important contribution to optimize efficiency of deradicalization for counterterrorism purposes.